No Effect of Return to Sport Test Batteries with and without Psychological PROs on the Risk of a Second ACL Injury: A Critical Assessment of Four Different Test Batteries - Ramana Piussi; Rebecca Simonson; Johan Högberg; Roland Thomeé; Kristian Samuelsson; Eric Hamrin Senorski (International Journal of Sports Physical Therapy)
# Background